Analisis Kualitas Instrumen Penilaian Berbasis Kelas untuk Mengukur Kompetensi Literasi Sains Peserta Didik SMA pada Materi Energi Terbarukan - Mukhayyarotin Niswati Rodliyatul Jauhariyah; Nadia Dewi Masithoh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this research is to analyze the quality of class-based instruments in the domains of knowledge, attitudes and skills to measure scientific literacy competency. This research uses a limited ADDIE research design consisting of Analyze, Design and Development stages. Data was collected using test and questionnaire methods. This research was tested on 30 Unesa Physics Education Study Program students. Theoretical validity results show that the assessment instrument prepared meets the valid category. The theoretical validity results were obtained from validation by 3 expert validators, namely 2 Unesa Physics Education lecturers and 1 MBI Amanatul Ummah Pacet Mojokerto teacher. Empirical validity was obtained from testing the assessment instrument on 30 active Unesa Physics Education students with a total of 15 questions. Then, the question item was declared valid with an rcount of 0.922 and an rtable of 0.361.